IN VITRO RELEASE MODELING OF ASPIRIN FLOATING TABLETS USING DDSOLVER - Agus Siswanto; Achmad Fudholi; Akhmad Kharis Nugroho; Sudibyo Martono (Indonesian Journal of Pharmacy, 2015)
Aspirin has low solubility in water therefore, dissolution is a rate limiting step for absorption. Floating tablet formulation is designed to improve the bioavailability of aspirin. The objective of this study was to determine in vitro dissolution study of aspirin floating tablet release kinetics model. The floating tablets were prepared by a direct compression method using Methocel K4M CR, NaHCO3, Ethocel, Aerosil, and dicalcium phospate anhydrous as excipients. Tablets were evaluated by different parameters such as physicochemical properties, floating lag time (Flag time), total floating time, and dissolution. The result showed that the tablet mass has good flow properties of 13.54 g/sec. Aspirin floating tablets had a weight uniformity (CV=1.45%), good hardness (6.42kg), and low friability (0.158%). The tablet has a short Flag time of 25.16 sec and long floating time of 8 hours. Dissolution data were evaluated using DDSolver conducted by (1) Statistical parameters: R2adjusted, AIC, MSC; (2) Visual goodness of fit (GOF). The results showed that aspirin floating tablets release kinetics followed the Korsmeyer-Peppas model. Aspirin release occurs through the mechanism of anomalous transport which combines Fickian diffusion and polymer relaxation.Key words: aspirin floating tablet, DDSolver, modeling of drug release